Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
[tex]\frac{1}{3}h -4(\frac{2}{3}h-3^{(3})=\frac{2}{3}h-6^{(3} \\\\ \frac{h}{3} -4*\frac{2h-9}{3}=\frac{2h-18}{3} \\\\ h-4(2h-9)=2h-18 \\\\ h-8h+36=2h-18 \\\\ -7h+36=2h-18 \\\\ -7h-2h=-18-36 \\\\ -9h=-54 \\\\ \boxed{h=\frac{-54}{-9}=6}[/tex]
[tex]\frac{1}{3}h-4(\frac{2}{3}h-3)=\frac{2}{3}h-6\ \ \ \ |multiply\ by\ 3\\\\
h-4(2h-9)=2h-18\\\\
h-8h+36=2h-18\\\\
-7h+36=2h-18\ \ \ |subtract\ 2h\\\\
-9h+36=-18\ \ \ |subtract\ 36\\\\
-9h=-54\ \ \ |divide\ by\ -9\\\\
h=6[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.